An Examination of the Multidimensionality of Supervisor and Subordinate Perceptions of Leader-Member Exchange - GREGURAS, Gary J. (Institutional Knowledge at Singapore Management University, 2006)
Research on leader-member exchange (LMX) theory typically has measured LMX in a unidimensional manner and has neglected supervisor perceptions of the LMX relationship. The present study developed and validated a multidimensional scale of supervisor LMX based on Liden and Maslyn's (1998) multidimensional subordinate LMX scale. Confirmatory factor analyses supported a multidimensional factor structure for both supervisor and subordinate LMX scales with four distinct dimensions: affect, loyalty, contribution, and professional respect. Results further indicated that these dimensions differentially predicted various criteria indicating that different aspects of the LMX relationship are of greater or lesser importance depending upon the criterion of interest. Additionally, results indicated that multidimensional LMX scales measured from both supervisor and subordinate perspectives predict important individual job attitudes and behaviours above scales that are either unidimensional or measured from just one perspective.